Genetic Phylogeny and Diversity of some Romanian Silkworms Based on RAPD Technique - Emilia Maria Furdui; Liviu Al. Mărghitaș; Daniel Dezmirean; Iulia Franceasca Pop; Cristian Coroian; Ioan Pașca (Scientific Papers Animal Science and Biotechnologies, 2023)
Randomly amplified polymorphic DNA (RAPD) markers were used in the present study to analyze genetic diversity and phylogenetic relationships among some race and hybrids of Romanian Bombyx mori. DNA from 8 hybrids and 1 race was amplified with 35 highly polymorphic RAPD primers, of which 21 markers generated polymorphic bands that were used to analyze genetic phylogeny and diversity. A total of 921 polymorphic bands were detected and UPGMA cluster analysis of Jaccard’s genetic distance grouped silkworm strains on the basis of their origin, obtaining a dendogram reflecting their genetic relationship